Identification of novel inhibitors targeting serine acetyltransferase from Neisseria gonorrhoeae - Keely E.A. Oldham; Wanting Jiao; Erica Prentice; Joanna L. Hicks (Computational and Structural Biotechnology Journal)
Neisseria gonorrhoeae is an obligate human pathogen and the etiological agent of the sexually transmitted infection, gonorrhoea. The rapid emergence of extensively antimicrobial-resistant strains, including those resistant to all frontline antibiotics, has led to N. gonorrhoeae being labelled a priority pathogen by the World Health Organization, highlighting the need for new antimicrobial treatments. Given its absence in humans, targeting de novo cysteine biosynthesis has been identified as a promising avenue for developing new antimicrobials against bacterial pathogens. The biosynthesis of cysteine is catalyzed by two enzymes; serine acetyltransferase (SAT/CysE) which catalyzes the first step and O-acetylserine sulfhydrylase (OASS/CysK) that catalyzes the second step incorporating sulfur to form l-cysteine. CysE is reported to be essential for bacterial survival in several bacterial pathogens including N. gonorrhoeae. Here, we have conducted virtual inhibitor screening of commercially available compound libraries against SAT from N. gonorrhoeae (NgSAT). We have identified a hit compound with an IC50 of 8.6 µM and analyzed its interactions with the enzyme’s active site. This provides a platform for the identification and development of novel SAT inhibitors to combat drug-resistant bacterial pathogens.